(3GdchGcH GdOQjI aj eOM NjQ GdHQjIs - (3eMeO Hf SYjO Hf MeGO Hf YHO Gddg GdUfgGLj GdHhUjQj GdeUQj, TQa GdOjf, CHh YHO Gddg , (B696 (3g` s ((3GdSjO eMeO Mdei s)
(3ChdgG (B:s
(3bGd GdTjN SHH EfTGFi gPg GdbUjOI GdeHGQcI Cfi cfJ bO GUGHfi NdW aGdL aCfTfCJ gPg GdbUjOI GdeHGQcI hfeJg aQGjJ GdfHi Udi Gddg Ydjg hSde aeSM HjOg GdeHGQcI aYhajJ dhbJi hUGYJi s
(3BNQgG (B:s
(3hGPf dSMH UdGI efc OGFeI Ydi GdfHi Hefgd hefSLe eGQfMJ YPHGJ GdHGf QjM UHG hCWQH GdYjS MGOi GdYjS HGdfZe s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdLRA (B2 - (3U (B1331 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B112 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs